(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2026)
Chronic rhinosinusitis (CRS) is a widespread condition influenced by various factors, including environmental pollution, allergies, and immune dysregulation. The presence of metabolic syndrome (MS) worsens the prognosis and exacerbates the course of the disease by increasing the inflammatory response and complicating management strategies. Therefore, studying the interaction between CRS and MS is essential for developing targeted therapeutic approaches.